Economic Report on Africa 2021 - United Nations Economic Commission for Africa (United Nations, 2022)
The report applies a poverty-vulnerability-resilience framework to examine the impact of COVID-19 on household well-being in Africa. The report emphasizes the dynamic nature of poverty since some of the poor are not poor all the time, though they are often vulnerable because of exposure to a multitude of risks that can push them below the poverty line and increase chronic poverty. Reducing vulnerability to risks is critical for enhancing well-being and reducing future poverty.